Karakteristik Ibu dan Bayi Dengan Sepsis Neonatorum Di Ruang Perinatologi Rumah Sakit Pendidikan Jawa Timur: Penelitian Awal - Amaliya, Sholihatul (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Neonatal sepsis is experienced more frequently in neonates with high mortality and morbidity. The clinicalsigns of neonatal sepsis are non-specific, thus the identification of the characteristics of infants and mothersthat may increase an infant’s risk of developing sepsis is important. This study aims to identify thecharacteristics of mothers and infants with sepsis. The descriptive retrospective was used with secondarydata from the student’s nursing care report in the Ners profession learning stage. Respondents involved were17 by convinience sampling. Inclusion criterias were babies diagnosed with sepsis and undergoing hospitaltreatment during the student rotation schedule. The results showed 53% of infants had early-onset neonatalsepsis, premature birth (53%), and low birth weight (65%). Characteristics of mothers 53% of spontaneousdeliveries and experiencing health problems (59%) such as infection, hypertension, and bleeding. Theconclusion of this study the majority of babies born premature and LBW with the mother’s characteristicshave spontaneous birth and experiencing health problems during pregnancy